If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying eln(2x + -3) = 1 Reorder the terms: eln(-3 + 2x) = 1 (-3 * eln + 2x * eln) = 1 (-3eln + 2elnx) = 1 Solving -3eln + 2elnx = 1 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Reorder the terms: -1 + -3eln + 2elnx = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + -3eln + 2elnx = 0 The solution to this equation could not be determined.
| 5+x-3=3x | | Y=2x4-128/152 | | 12c-7-3c+9= | | 6x^2-36x-96=0 | | 8z+6z= | | 2ln(2x-3)=2 | | 32=-16t+56t | | x^2+y^2+12x+4y+36=0 | | 2s+7s= | | 21y+7y= | | 2x+x+10=55 | | 86x+5x-8y-800=500 | | 5p+5p= | | 3x(x-2)=-1.5 | | 13b+7b= | | 4w+2=4w+7 | | 2x+8-3=11+11+11 | | w*3=7 | | 29r+4=28+1r | | (w/(2w-3))=4/w | | 4x^2+24x+4y^2+4y-363=0 | | 6x-39=3x+42+11x | | 5.98t=1.4t-13.53 | | 2r(x-3)=15 | | a=6-2b | | 6x+9-8(x+1)=3x+5 | | -2=-(n-a) | | x*4=15 | | 5x+13=5(2+2x)-8x | | (x+3)2=-3+k | | (3u+2)(7+u)=0 | | 7(y+6)+7y=9 |